1986
DOI: 10.1177/153944928600600503
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study of Job Burnout among Hospital-Based Occupational Therapists

Abstract: Job-related stress over a prolonged period may lead to feelings of exhaustion, commonly referred to as burnout. Little is known, however, about the prevalence of such conditions among occupational therapists. This study addressed the following general research questions: Is burnout a significant problem among hospital-based registered occupational therapists (OTRs)? Is the Maslach Burnout Inventory (MBI) an appropriate instrument for measuring burnout of OTRs? Do specific OTR subgroups score differently on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
1

Year Published

1992
1992
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 14 publications
1
14
1
Order By: Relevance
“…The findings from this study indicated that work involvement, a large number of clients in one's caseload diagnosed with schizophrenia, work pressure, age, income level, the length of time working in psychiatric occupational therapy, size of caseload and the amount of overtime performed on a weekly basis were significant predictors of burnout. Unlike some of the earlier studies (Sturgess and Poulsen, 1983;Brollier et al, 1986;Rogers and Dodson, 1988), the mean score for emotional exhaustion for all respondents was significantly higher than that of the normative group of the MBI. This was found to be influenced by the particularly high scores of the senior therapists.…”
Section: Managerial Rolecontrasting
confidence: 98%
See 2 more Smart Citations
“…The findings from this study indicated that work involvement, a large number of clients in one's caseload diagnosed with schizophrenia, work pressure, age, income level, the length of time working in psychiatric occupational therapy, size of caseload and the amount of overtime performed on a weekly basis were significant predictors of burnout. Unlike some of the earlier studies (Sturgess and Poulsen, 1983;Brollier et al, 1986;Rogers and Dodson, 1988), the mean score for emotional exhaustion for all respondents was significantly higher than that of the normative group of the MBI. This was found to be influenced by the particularly high scores of the senior therapists.…”
Section: Managerial Rolecontrasting
confidence: 98%
“…However, the senior staff usually received little formal training in supervision, which may in itself be an additional stressor. Some previous research has shown that supervisory clinicians generally experience higher levels of burnout than staff clinicians (Brollier et al, 1986(Brollier et al, , 1987.…”
Section: Supervisionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brollier, Bender, Cyranowski & Velletri (1986) demonstrated that burnout among a sample of American occupational therapists did not vary according to the area of clinical practice or the amount of direct client contact time. In subsequent research, Brollier and her colleagues determined that employment in specialized clinical centres appeared to provide clinicians with more feelings of personal accomplishment and hence less burnout than employment in more general settings (Brollier, Bender, Cyranowski & Velletri, 1987a). Rogers & Dodson (1988) examined the level of burnout experienced by a sample of occupational therapists employed in the southeastern United States.…”
Section: Burnout In Occupational Therapymentioning
confidence: 99%
“…An initial search of the literature indicated that there had been little attention paid to distinguishing the work-related stressors or the experienced levels of stress within different practice arenas of occupational therapy, even though some specialties are likely to be more stressful than others. The review by Sweeney and Nichols (1996) incorporated studies that identified occupational therapists working in the mental health arena (Sturgess and Poulsen 1983, Brollier et al 1986, Rogers and Dodson 1988, Sweeney et al 1991, 1993a. A more systematic search conducted by the present research team, however, identified a number of additional papers (Brollier 1985, Madill et al 1987, Kraeger and Walker 1993, Allan and Ledwith 1998, which indicated the need for the review in this subject area to be updated.…”
Section: Deborah Edwards and Philip Burnardmentioning
confidence: 99%